Zakat Revolution: Opening The Door to Social Welfare in the Digital Era - Wahyudi, Ickhsanto; Yama, Indo; Said, Muhammad (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
Zakat, as an Islamic social financial instrument, has great potential in poverty alleviation and improving social welfare. However, the gap between the potential and realization of zakat collection is still significant. This study aims to evaluate the zakat management policy framework in the context of social welfare using the Systematic Literature Review (SLR) method with the PRISMA approach. Of the 64 articles identified in the Scopus database, 35 articles met the inclusion criteria for in-depth analysis. The review results revealed seven main themes: regulatory and legal framework, governance and management, technological innovation, distribution and empowerment strategies, public awareness and education, interinstitutional collaboration, and impact measurement and evaluation. The findings indicate that effective zakat management requires a holistic approach, including legal harmonization, managerial professionalism, technology adoption, innovative distribution models, public education, inter-institutional synergy, and a comprehensive evaluation system. This study recommends policy reforms that include improving regulations, standardizing management, integrating technology, developing empowerment programs, digital-based education campaigns, strengthening collaboration, and developing an evaluation framework integrated with the SDGs. The implementation of these recommendations is expected to optimize the role of zakat in improving social welfare in the digital era.